THE INFLUENCE OF PERMISIVE PARENTING ON SOCIAL EMOTIONAL DEVELOPMENT OF CHILDREN IN KINDERGARTEN NEGERI SUPERVISOR WEST PONTIANAK - Christiani Bintang Putri; Muhamad Ali; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the effect of permissive parenting on the socio-emotional development of children aged 5-6 years in TK Negeri Pembina West Pontianak. The method used in this research is quantitative in the form of relationship studies. The data collection technique use indirect communication techniques. Data collection tools using questionnaires. Permissive parenting and social-emotional development questionnaires were given to parents because kindergarten children can give a bias answer about themselves. Data validity uses Product Moment correlation. Data reliability using Alpha Cronchbach's technique. The questionnaires were analyzed using simple linear regression and t-test. The results of this study indicate that there is a positive influence between permissive parenting patterns on social emotional development aged 5-6 years in TK Negeri Pembina West Pontianak with a regression coefficient value of 0.654 with t test which shows that t count is greater than t table (2.143 > 2,101) which means Ho is rejected and Ha is accepted. Thus, permissive parenting has an influence on the socio- emotional development of children aged 5-6 years in TK Negeri Pembina West Pontianak.